Production of Cellulose From Bamboo Shoot Shell Using Hydrothermal Technique - Kanjana Manamoongmongkol; Rachit Suwapanich; Lamphung Phumjan; Woatthichai Narkrugsa; Pongsert Sriprom (Journal of the Japan Institute of Energy, 2021)
The preparation and characterization of purified cellulose from bamboo shoot shell were studied using fouriertransform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The preparation of cellulose fiber included extraction of cellulose from bamboo shoot shell by treatment with 5 % NaOH and 4 % H2O2, and purification of cellulose fiber using hydrothermal technique. The result showed that cellulose has been successfully extracted at a 32.56% yield by the 5% NaOH / 4% H2O2 treatment, and the purified cellulose was produced using autoclaving at the temperature of 120 °C and pressure at 0.1 MPa for 2 h 5 min, with the % recovery of purified cellulose around 94.08. Bamboo shoot shell and cellulose sample were further characterized using FTIR technique. It was found that the 5% NaOH / 4% H2O2 treatment eliminated lignin and hemicellulose from bamboo shoot shell but did not affect cellulose. The hydrothermal technique did not affect the destruction of the cellulose structure as well. Comparison of the SEM image showed that cellulose was separated into individual microfibers after the 5% NaOH / 4% H2O2 treatment while the SEM image of purified cellulose was the small thread-like fibers with smoother surface. Therefore, hydrothermal treatment can be performed for purification of cellulose.
Keywords: Advanced Cellulose Research Studies; Natural Fiber Reinforced Composites; Lignin and Wood Chemistry